Odpowiedź :
Odpowiedź:
b)
2(x- 2y) - 2(y -x+ 1,5) =5
(2-x)/5 - 0,3y = 0 | * 5
2x- 4y- 2y+2x - 3 = 5
2 - x - 0,3y * 5 = 0
4x - 6y = 5 + 3
- x - 1,5y = - 2
4x - 6y = 8 | : 2
- x - 1,5y = - 2 | * 2
2x - 3y = 4
- 2x - 3y = - 4
dodajemy równania
2x - 2x - 3y - 3y = 4 - 4
- 6y = 0
y = 0
- x - 1,5y = - 2
- x - 1,5 * 0 = - 2
- x - 0 = - 2
- x = - 2
x = 2
Jedno rozwiązanie
c)
x - 7(y - 1) = - 2(5/2 + x )
-2(1 - 2x - y) = 1 - x - 5y
x - 7y + 7 = - 5 - 2x
- 2 + 4x + 2y = 1 - x - 5y
x + 2x - 7y = - 5 - 7
4x + 2y + x + 5y = 1 + 2
3x - 7y = - 12
5x + 7y = 3
dodajemy równania
3x + 5x - 7y + 7y = - 12 + 3
8x = - 9
x = - 9/8 = - 1 1/8
3x - 7y = - 12
3 * (- 9/8) - 7y = - 12
- 27/8 - 7y = - 12 | * 8
- 27 - 56y = - 96
- 56y = - 96 + 27 = - 69
56y = 69
y = 69/56 = 1 13/56
Jedno rozwiązanie
d)
3(1 - x) - 5(2 - y) =5
0,2(2- 3x) + y = 0,8
3 - 3x - 10 + 5y = 5
0,4 - 0,6x + y = 0,8 | * 10
- 3x + 2y = 5 - 3 + 10
4 - 6x + 10y = 8
- 3x + 2y = 12 | * ( - 2)
- 6x + 10y = 8 - 4 = 4
6x - 4y = - 24
- 6x+ 10y = 4
dodajemy równania
6x - 6x - 4y + 10y = - 24 + 4
6y = - 20
y = - 20/6 = - 3 2/6 = - 3 1/3
6x - 4y = - 24
6x - 4 * (- 20/6) = - 24
6x + 80/6 = - 24
6x + 13 2/6 = - 24
6x = - 24 + 13 2/6 = - 24 + 13 1/3 = - 23 3/3 + 13 1/3 = - 10 2/3
x = - 10 2/3 : 6 = - 32/3 * 1/6 = - 16/3 * 1/6 = - 18/18 = - 1
Jedno rozwiązanie